Fatwa dan Ijtihad Umar bin Khaththab: Ensiklopedia Berbagai Persoalan Fiqih - HALAWI, Muhammad Abdul Aziz (Risalah Gusti, 2003)
Fatwa dan Ijtihad Umar bin Khaththab: Ensiklopedia Berbagai Persoalan Fiqih